Converting Agro-Ecological Waste into Potential Substrates for Cultivation of P. ostreatus - Lim, Jia Hui; Geetha, Subramaniam; Nabil, Sanusi; Cheng, Wan Hee; Wong, Ling Shing (INTI International University, 2022)
Pleurotus ostreatus is an edible mushroom which is rich in proteins, carbohydrates, vitamins, minerals and lipids, making it a highly beneficial food source. Commercial cultivation of P. ostreatus is mostly done on sawdust, however, there is a potential shortage of sawdust due to a shift of rubber plantations to more profitable oil palm plantations in Malaysia. Therefore, alternative substrates should be sourced, preferably from agricultural waste. Cultivation of P. ostreatus on agricultural waste that are abundant in Malaysia, namely Imperata cylindrica, was studied in terms of cultivation parameters and nutritional value. The sterilized substrates were treated and inoculated with spawn of P. ostreatus before incubation for colonization and fruiting of the mushrooms. The experiment was conducted in triplicates for each substrate. I. cylindrica had a faster mycelial growth compared to sawdust which was used as a control. After complete colonization, two flushes of matured fruiting bodies were harvested from both sawdust and I. cylindrica, where P. ostreatus cultivated on I. cylindrica took a shorter duration (58 days). Although I. cylindrica had better mycelial growth, however a lower yield performance and biological efficiency were observed with this substrate compared to sawdust. However, the two different substrates had similar effects on the nutritional values of P. ostreatus in terms of the moisture, total carbohydrates, protein, lipids and metabolised energy. Based on the results obtained, I. cylindrica was found to be a potential alternative substrate for P. ostreatus cultivation as no significant differences were observed on the total yield and nutritional values between substrates. Nevertheless, further studies on the optimization of commercial P. ostreatus production using I. cylindrica are required.